(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the conceptual structure of the individual and its psychological nature. The study highlights the role of personality theories, the professioniogram and psychogram in the formation of a psychological portrait, as well as the modern requirements for a specialist by international organizations such as IAAP and ICP. The correlation of the psychological and socio-psychological portraits is scientifically substantiated, linking the internal conceptual system of the individual with the social environment.